2014
DOI: 10.1016/j.cpc.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Monte Carlo methods for lattice systems: A first look

Abstract: a b s t r a c tWe investigate the applicability of quasi-Monte Carlo methods to Euclidean lattice systems for quantum mechanics in order to improve the asymptotic error behavior of observables for such theories. In most cases the error of an observable calculated by averaging over random observations generated from an ordinary Markov chain Monte Carlo simulation behaves like N −1/2 , where N is the number of observations. By means of quasi-Monte Carlo methods it is possible to improve this behavior for certain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
(107 reference statements)
0
25
0
Order By: Relevance
“…When the extent of the time lattice is kept short, T 1.5, both, QMC and recursive numerical integration show a comparable performance with an improved error scaling which is faster than 1/ √ N . However, as noted in [7] QMC becomes inefficient when the time extent T is made larger than T = 1.5, independent of the value of the lattice spacing a.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When the extent of the time lattice is kept short, T 1.5, both, QMC and recursive numerical integration show a comparable performance with an improved error scaling which is faster than 1/ √ N . However, as noted in [7] QMC becomes inefficient when the time extent T is made larger than T = 1.5, independent of the value of the lattice spacing a.…”
Section: Discussionmentioning
confidence: 86%
“…Adding a non-Gaussian term in case of the anharmonic oscillator, we found α ≈ 0.75 which is not optimal but significantly better than the error scaling of MCMC methods. However, it needs to be mentioned that for certain system sizes, that is, large Euclidean times, the QMC method did not work particularly well for the anharmonic oscillator and no error scaling improvement could be established; cf., [7] for details.…”
Section: Introductionmentioning
confidence: 99%
“…A mathematical review of the QMC approach can be found in [1]. The major part of this contribution is based on our paper [2] (cf. also [3]).…”
Section: Motivationmentioning
confidence: 99%
“…The QMC approach provides the potential to circumvent the aforementioned problems, as it exhibits certain favorable properties. Most importantly, it is able to improve the error scaling to N −1 , given that certain conditions are met (see [2]). It is further encouraging to realize that the QMC technique has already been applied successfully in other fields like financial mathematics [4] for example.…”
Section: Motivationmentioning
confidence: 99%
“…Therefore, alternative approaches to MC-MC methods need to be developed and in [5,6] we have proposed and tested Quasi Monte Carlo and iterated numerical integration techniques. These methods can improve the convergence of the involved integrations and also have the potential to deal with the sign problem.…”
Section: Introductionmentioning
confidence: 99%